REFUGEE BASED DATA COLLECTION IN DISASTER RESPONSE - Muhammad Lulu Latif Usman; Fifing Fifing; Asep Adang Supriyadi; Luthfiyah Sakinah (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Indonesia's high disaster risk requires an information system that can improve effectiveness in disaster response. Therefore, there is a need for an application that could be a means for various information in disaster response in Indonesia. This research uses the Development Life Cycles or SDLC Software, specified with the Waterfall Model. This model has 4 phases, as following: requirement analysis, system analysis, implementation, verification, and maintenance. From this research, a victim-based data collection application can collect data at the disaster site regularly. It also can replace the previous conventional methods so that it can facilitate the National Disaster Management Authority (BNPB) in carrying out information to the community. The results of this study are the prototype of data collection applications in helping disaster response.